Exploration on the Design and Application of a Traditional Chinese Medicine Chinese Language Assistance Practice and Testing Tool Based on WeChat Mini-Programs - Cao, Meng; Liu, Na (Journal of Contemporary Medical Practice, 2025)
As we all know, Chinese medicine is a discipline, so the language of Chinese medicine is a scientific language. However, TCM is bred in traditional Chinese culture and deeply influenced by Chinese culture. TCM language has a distinct humanistic color. Compared with daily language, it is more difficult for foreign students to learn TCM language. If we can integrate most Chinese courses of TCM in the market, classify new words, texts and professional terms, and design and develop a small program that can consolidate and test Chinese knowledge of TCM for foreigners, it will help foreign students to better learn Chinese knowledge and master Chinese terminology.